STUDY ON THE SOUND ABSORPTION CHARACTERISTICS OF WOOD FROM SCOTS PINE (Innovation in Woodworking Industry and Engineering design, 2026)
In this paper, the absorption properties of wood materials from Scots pine (Pinus Silvestrys L.), which are widely used in flooring and wall linings, have been experimentally studied. The frequency-dependent sound absorption coefficient (αp) was determined in octagonal frequency bands with an average geometric frequency of 100 Hz to 2000 Hz. The tests were carried out using an impedance tube, according to the requirements of BDS EN ISO 10534-1:2006. The obtained results are of a particular interest from both scientific and practical point of view, given that the sound absorption coefficient has a decisive impact on the reverberation time. The latter is the main acoustic parameter of a room depending on its intended purpose.